ANALISIS POTENSI LISTRIK PADA TEKNOLOGI TEPAT GUNA KINCIR AIR - Arrizka Yanuar Adipradana; Hery Teguh Setyawan; Apanggi Mustakhim (Jurnal Teknologi, 2022)
Streams can be used for micro and pico-scale power plants. Water wheel technology has long been used by the community to raise river water to rice fields by utilizing the spinning wheel. Farmers in Gedongan Hamlet, Bondowoso Village, Magelang Regency have long used this technology as a pump to raise river water to rice fields that are elevated above the river. From the literature review it is known that the cross flow turbine from a waterwheel can produce energy by working the rotation and torque of the wheel. However, the appropriate technology has not been used as a piko power generator. The purpose of this study is to determine the amount and power of energy produced by waterwheels so that the potential electricity produced is known. The benefit of the research is that it can increase electrification in rural areas, especially for street lighting with cheap, environmentally friendly and sustainable technology. The research method was carried out by collecting primary data in the field by measuring the amount of rotation of the watermill due to river velocity. The research stages carried out are selecting a specific research location, preparing tools and materials such as waterwheels, rpm meters and tacho meters, mobilizing measuring instruments, collecting field data, analyzing data, compiling results and reports. Based on research that has been done, the electric potential generated by traditional waterwheels is 80 watts, while the electrical energy generated from the spinning wheel is 7.5 watts.